Improving Amazon EC2 Spot Instances Price Prediction using Machine Learning Algorithm - M. Prasanthi,; G.Chishma,; P. Padmavathi,; K. Reethika,; A. Chandra Sekhar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Spot instances were introduced by Amazon EC2 in December 2009 to sell its spare capacity through auction based market mechanism. Despite its extremely low prices, cloud spot market has low utilization. Spot pricing being dynamic, spot instances are prone to out-of bid failure. Bidding complexity is another reason why users today still fear using spot instances. This work aims to present Regression Random Forests (RRFs) model to predict one-week-ahead and one-day-ahead spot prices. The prediction would assist cloud users to plan in advance when to acquire spot instances, estimate execution costs, and also assist them in bid decision making to minimize execution costs and out-of-bid failure probability. Simulations with 12 months real Amazon EC2 spot history traces to forecast future spot prices show the effectiveness of the proposed technique. Comparison of RRFs based spot price forecasts with existing non-parametric machine learning models reveal that RRFs based forecast accuracy outperforms other models. We measure predictive accuracy using MAPE, MCPE, OOBError and speed. Evaluation results show that
Keywords: Amazon EC2; Compute instances; One-day-ahead prediction; One-week-ahead prediction; Regression Random Forests; Spot instances; Spot price prediction